EXPERIMENTAL STUDY OF THE MECHANICAL CHARACTERISTICS OF MORTARS PRODUCED WITH A BINDER CONTAINING TWO COW DUNG ASHES - HOUEHANOU, ERNESTO CABRAL; AHLINHAN, MARX FERDINAND; OLODO, ESSÈ TIMOTHÉE EMMANUEL; GBAGUIDI AÏSSE, GÉRARD LÉOPOLD; DEGAN, GÉRARD (My University, 2018)
This study concerns the evaluation of the mechanical characteristics of five mortars produced with a binder containing different proportions of cow dung ash produced in laboratory with objective to its using as additional mineral in the production of mortars. Five other mortars are produced with the same binder containing the same proportions cow dung ash produced traditionally and a standard mortar (control) is also produced with the same binder without any mineral in addition. Some compressive strength tests are carried out on test specimens of mortar (40x40x160 mm3). The compressive strength and chemical characteristic allowed us to estimate and to compare the mechanical characteristics and the pozzolanic activity ratio of both used ashes. The pozzolanic activity ratio of both types of cow dung ash is estimated to 75% and 68% in 28 days. The mechanical characteristics of the mortars containing some cow dung ash produced in laboratory are superior for the greater part to those of the mortars containing some cow dung ash produced traditionally. On the other hand, the medium-term (56 and 90 days) mechanical characteristics of the mortars containing until 15 % of cow dung ash produced in laboratory are equivalent to those of reference mortar.
Keywords: cow dung ash; additional mineral; mechanical characteristics; pozzolanic activity